ANALISIS DINAMIKA LEVY FLIGHT DAN PREDIKSINYA DENGAN METODE ANFIS (STUDI KASUS 3 SAHAM OPERATOR SELULER DI INDONESIA) - Saldi, Ari
Complex system is a field of science that discusses the process of small parts of the system that compiles the collective collection of the universal system and the process of the system is related to the surrounding environment. One example of the study of complex systems is econophysics which discusses studies between economic and physical agreements. This study discusses market finance to analyze and analyze the dynamics of flight levies and to predict flight levies using the Adaptive Neuro Fuzzy Inference System (ANFIS) method with a variety of parameters. The issued shares are shares of Indonesian cellular operators listed on the Indonesian stock exchange, namely Telkomsel (TLKM), XL-Axiata (EXCL) and Indosat (ISAT) in the range of April 2012 - April 2019. Based on descriptive research results with stability index data (?) less than 2 and several other parameters are also carried out in a simulation of the trajectory, obtained, traffic, extortion, extortion, retainer, retainer, TLKM, EXCL and ISAT using the gaussian membership function parameter (gaussmf).